Role of trace amine‑associated receptor 1 in the medial prefrontal cortex in chronic social stress-induced cognitive deficits in mice. (May 2021) - Zhang, Yue; Li, Ji-Tao; Wang, Han; Niu, Wei-Pan; Zhang, Chen-Chen; Zhang, Yanan; Wang, Xiao-Dong; Si, Tian-Mei; Su, Yun-Ai
Abstract: Emerging evidence supports an essential role of trace amine-associated receptor 1 (TAAR1) in neuropsychiatric disorders such as depression and schizophrenia. Stressful events are critical contributors to various neuropsychiatric disorders. This study examined the role of TAAR1 in mediating the negative outcomes of stressful events. In mice that experienced chronic social defeat stress but not acute stress, a significant reduction in the TAAR1 mRNA level was found in the medial prefrontal cortex (mPFC), a brain region that is known to be vulnerable to stress experience. Conditional TAAR1 knockout in the mPFC mimicked the cognitive deficits induced by chronic stress. In addition, chronic treatment with the selective TAAR1 partial agonist RO5263397 ameliorated chronic stress-induced changes in cognitive function, dendritic arborization, and the synapse number of pyramidal neurons in the mPFC but did not affect chronic stress-induced anxiety-like behaviors. Biochemically, chronic stress reduced the ratio of vesicular transporters of glutamate-1 (VGluT1) / vesicular GABA transporter (VGAT) in the mPFC，most prominently in the prelimbic cortex, and RO5263397 restored the excitatory-inhibitory (E/I) imbalance. Together, the results of this study reveal an essential role of TAAR1 in mediating chronic stress-induced cognitive impairments and suggest that TAAR1 agonists may be uniquely useful to treat MDD-related cognitive impairments. Graphical Abstract: ga1 Highlights: Chronic social defeat stress (CSDS) downregulated the TAAR1 mRNA level in the medial prefrontal cortex (mPFC) in mice. Conditional TAAR1 knockout in the mPFC mimicked the cognitive deficits induced by CSDS. TAAR1 partial agonist RO5263397 treatment restored most of the negative effects caused by CSDS in the mPFC. TAAR1 in the mPFC is involved in the regulation of chronic stress vulnerability. The regulation of E/I balance may be an important contributor underlying the anti-stress effect of TAAR1 agonists.